1993
DOI: 10.1136/oem.50.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Markers of early renal changes induced by industrial pollutants. I. Application to workers exposed to mercury vapour.

Abstract: Several markers of renal changes have been measured in a cohort of 50 workers exposed to elemental mercury (Hg) and in 50 control workers. After application of selection criteria 44 exposed and 49 control workers were retained for the final statistical analysis. Exposed workers excreted on average 22 micrograms Hg/g creatinine and their mean duration of exposure was 11 years. Three types of renal markers were studied--namely, functional markers (creatinine and beta 2-microglobulin in serum, urinary proteins of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 46 publications
6
54
0
3
Order By: Relevance
“…Generally, transient immunologic changes may occur after exposure to mercuric chloride. Only one epidemiologic study has reported an elevation of anti-GBM however (3), and elevation is contradicted by several nonpositive investigations (4,(8)(9)(10)(13)(14)(15).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Generally, transient immunologic changes may occur after exposure to mercuric chloride. Only one epidemiologic study has reported an elevation of anti-GBM however (3), and elevation is contradicted by several nonpositive investigations (4,(8)(9)(10)(13)(14)(15).…”
mentioning
confidence: 82%
“…Cross-sectional studies of workers during ongoing exposure to mercury vapor have shown an elevated activity of the kidney proximal tubular cell enzyme N-acetyl-β-D-glucosaminidase in urine (U-NAG) or associations between U-NAG and the mercury concentration in urine (U-Hg) (4,5,(7)(8)(9)(10). Increased U-NAG activity in chloralkali workers has been associated with exposure levels corresponding to U-Hg of about 5 nmol/ mmol creatinine (10).…”
mentioning
confidence: 99%
“…Through the use of biomarkers of damage to various parts of the nephron, a pattern of damage is emerging that is consistently observed now both in U.S. and European studies of men occupationally exposed to cadmium (4)(5)(6)(7)(8)(9)(10) The lowest observed effect is indicated by a significant prevalence of abnormal 6-keto-prostaglandin Fla (6-keto-PGFi,a) and sialic acid levels in urine at an approximate urine cadmium concentration of 2.4 nmol Cd/mmol creatinine (2.4 pg Cd/g creatinine) (10). Proteins such as albumin and transferrin originate in the plasma and are filtered to a limited degree through the glomerulus, and the protein that is filtered is primarily reabsorbed by the tubules.…”
Section: Thresholds Of Effects: Cadmiummentioning
confidence: 99%
“…Some of these candidate markers are beginning to be examined in human studies. Excretion of fibronectin has been examined in relation to exposure to three heavy metals (cadmium, lead, and mercury), with no significant changes in excretion seen in the exposed groups (7)(8)(9).…”
Section: Potential New Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation